Self-Reported Periodontal Disease and its Association with Dental Anxiety in Lagos, Nigeria - Modupeore Ekua Sorunke; Olubunmi O. Onigbinde; Afolabi Oyapero; Olurotimi A. Coker (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the relationship between dental anxiety and self-reported periodontal status. Material and Methods: The study was conducted among 263 patients at the Family Medicine Clinic of the Lagos State University Teaching Hospital (LASUTH), Ikeja, Lagos, Nigeria. Self-assessed gingival and periodontal disease was measured using the validated periodontal disease self-report surveillance questionnaire. The Modified Dental Anxiety Scale (MDAS) was used for evaluating dental anxiety. Student's t-test was used to test for association between categorical variables. P-value < 0.05 was considered to be statistically significant. Results: Seventy-seven (29.3%) participants had high dental anxiety, while 49 (18.6%) had very high dental anxiety. The prevalence of periodontal disease was higher among those with very high dental anxiety (77.6%), while female respondents had a significantly higher proportion of self-reported periodontitis (34.1%). There was a significantly higher prevalence of very high dental anxiety among respondents who had never visited the dentist (23.2%). Similarly, females (19.4%), middle-class respondents (30.8%), and those with a primary level of school education (23.5%) had a higher prevalence of high dental anxiety, even though the association was not significant. Conclusion: The prevalence of self-reported periodontal disease among the respondents with very high dental anxiety was higher than in those with high dental anxiety and those without dental anxiety, but the difference was not significant.